A comparison of soil tests for available phosphorus in long‐term field experiments in Europe. (23rd October 2017) - Nawara, S.; Van Dael, T.; Merckx, R.; Amery, F.; Elsen, A.; Odeurs, W.; Vandendriessche, H.; Mcgrath, S.; Roisin, C.; Jouany, C.; Pellerin, S.; Denoroy, P.; et al.
Summary: Most soil tests for available phosphorus (P) perform rather poorly in predicting crop response. This study was set up to compare different established soil tests in their capacity to predict crop response across contrasting types of soil. Soil samples from long‐term field experiments, the oldest >100 years old, were collected in five European countries. The total number of soil samples ( n = 218), which differed in cropping and P treatment, and originated from 11 different soil types, were analysed with five tests: ammonium oxalate (Ox), ammonium lactate (AL), Olsen P, 0.01m CaCl2 and the diffusive gradient in thin film (DGT). The first three tests denote available P quantity (Q), whereas the last two indicate P intensity (I) of the soil solution. All five tests were positively related to the crop yield data ( n = 317). The Q‐tests generally outperformed I‐tests when evaluated with goodness of fit in Mitscherlich models, but critical P values of the I‐tests varied the least among different types of soil. No test was clearly superior to the others, except for the oxalate extraction, which was generally poor. The combination of Q‐ and I‐tests performed slightly better for predicting crop yield than any single soil P test. This Q + I analysis explains why recent successes with I‐tests (e.g. DGT) were found for soils with larger P sorption than for those in the present study. This systematic evaluation of soil tests using a unique compilation of established field trials provides critical soil P values that are valid across Europe. Highlights: We compared soil P tests for predicting crop response across contrasting soil types. No test was clearly superior to the others except for the oxalate extraction, which was generally poor. This study suggests that intensity tests do not perform markedly better than quantity tests. The evaluation of soil P tests on this unique dataset provided critical soil P values across Europe.